Modern China, 1840-1972 : an introduction to sources and research aids - Nathan, Andrew J. (Andrew James) (Michigan papers in Chinese studies, 1973)
Graduate students have traditionally learned a good part of what they know about sources and research aids on modern China through hearsay and serendipity, in unsystematic and unreliable bits and pieces. The field has now developed to the point where this need not and ought not to be so. It is now possible for beginning researchers to start with some shared basic knowledge of research aids and documentary resources. This research guide is meant to provide that knowledge. The user of this guide is envisaged as an American graduate student in history or the social sciences who is already familiar with the major English-language secondary literature on modern China and is about to begin original research, either for a seminar paper or for a dissertation.